PENGARUH PENERAPAN METODE BERMAIN PERAN TERHADAP KETERAMPILAN MENCERITAKAN ISI DONGENG PADA PESERTA DIDIK KELAS III SEKOLAH DASAR - Agnes Asri; Frederiksen Novenrius Sini Timba; Desi Maria El Puang (Universitas Muhammadiyah Purwokerto, 2023)
The use of learning methods has considerable benefits in learning. Based on the results of observations on grade III students of SD Inpres Nogodue, the problems found by students who have not been able to read, and write are not neat and the teacher has not used the right learning method following the material taught. In general, teachers use the method of lectures and questions and answers. This condition results in the low ability of students to retell the content of fairy tales. As for the solution to this problem is to use the role-playing method. The type of research used is quantitative with experimental models. The research design used one group pretest and posttest design with a sample of 8 students. Research techniques using. The results showed that the average pretest value was 77.50, while the average posttest value was 87.50 with the hypothesis test results obtained a signification value (2-tailed) of 0.000 ≤ 0.005 then Ha was accepted and Ho was rejected. These results show that there is an influence on the use of role-playing methods on the skills of telling the content of students' fairy tales in subjects Indonesian grade III SD Inpres Nogodue.